CGE Modeling of Market Access in Services - Elisabeth M. Christen; Joseph Francois; Bernard Hoekman (Johannes Kepler University of Linz, Department of Economics, 2012)
This paper examines how the applied multi-sector computable general equilibrium (CGE) literature has moved into quantification of the impacts of greater market access for services. This includes discussion of multisector linkages to the service sector, as well both measuring barriers to trade and investment (generally with a mix of firm surveys, price comparisons, and econometrics), and how changes in these barriers, however measured, have been implemented in the CGE literature. Three challenges are highlighted. The first is identification of how trade in services takes place and how market access is therefore affected by policy. The second is to find data sufficiently robust for modeling purposes. The third, linked to the data problem, is to quantify the barriers to be examined. Significant progress has been made in modeling foreign direct investment and linking this to productivity, which turns out to be important. The paper also provides an example of modeling productivity linkages to openness and domestic regulation, with an applied CGE model of Italy. This illustrates cross-sector linkages and the integration of economic data and policy measures to define service sector experiments. Priorities for future research include better modeling of market structure, the linkages between sectors and the complementarities between different modes of supplying services.
Keywords: F10; 330; Trade in services; nontariff measures; nontariff barriers; regulation; FDI; productivity; liberalization; CGE.; Internationaler Dienstleistungsverkehr; Nichttarifäre Handelshemmnisse; Direktinvestition; Produktivität; Außenhandelsliberalisierung; CGE-Modelling; Allgemeines Gleichgewicht; Italien